THE USE OF PROJECT BASED LEARNING (PJBL) MODEL TO INCREASE STUDENTS’ ACTIVE PARTICIPATION IN SPEAKING CLASS AT SMAN 1 KERUAK - Sugianto, Sugianto; Sopian Saori (Sinar Lima, 2025)
Observations at SMAN 1 KERUAK show that students' active participation in speaking classes is still low, so appropriate intervention is needed in the learning process. Student activeness in learning is an important and fundamental issue that every teacher must understand, realize, and develop in the learning process. The purpose of this research is to find out how the use of project-based learning (PjBL) can increase students' active participation in speaking class at SMAN 1 Keruak. This research focused on class XI students at SMAN 1 KERUAK for the 2023–2024 academic year. The research method used is Classroom Action Research (CAR). The results of the data obtained from observation sheet show that students can fulfilled all of indicators of active participation, and the data field notes show that after using the project-based learning (PjBL) model, students became more actively participate in speaking class, and the data questionnaire show that the use of project-based learning (PjBL) model getting a positive response from all students totaling 34 stuents with an overall score of 93.52%. Based on the findings, it could be concluded that the use of project-based learning (PjBL) model can increase students' active participation in speaking class at SMAN 1 KERUAK.